Catheter Ablation for Ventricular Tachycardia in Patients with an Implantable Cardioverter Defibrillator (CALYPSO) Pilot Trial. (30th November 2014) - AL‐KHATIB, SANA M.; DAUBERT, JAMES P.; ANSTROM, KEVIN J.; DAOUD, EMILE G.; GONZALEZ, MARIO; SABA, SAMIR; JACKSON, KEVIN P.; REECE, TAMMY; GU, JOAN; POKORNEY, SEAN D.; GRANGER, CHRISTOPHER B.; HESS, PAUL L.; et al.
Catheter Ablation for Ventricular Tachycardia Introduction We conducted this pilot randomized clinical trial to determine the feasibility of a large clinical trial aimed at testing whether early use of catheter ablation of ventricular tachycardia (VT) is superior to antiarrhythmic medications at reducing mortality. Methods and Results Patients were enrolled at 4 sites if they had ischemic heart disease, an implantable cardioverter defibrillator (ICD), and received ≥1 ICD shock or ≥3 antitachycardia pacing therapies for VT. Patients were randomized to 2 arms: (1) antiarrhythmic medication (n = 14) and (2) catheter ablation (n = 13); patients were followed at 3 and 6 months. Endpoints included recurrent VT, time to first ICD therapy for VT, and death. Of 243 screened patients, 27 were enrolled. Main reasons for screen failures were: (1) patient was already on an antiarrhythmic medication (88 [41%]), (2) VT due to a reversible cause (23 [11%]), and (3) incessant VT (20 [9%]). Fourteen patients had recurrent VT, 8 (62%) in the ablation arm and 6 (43%) in the antiarrhythmic medication arm. Median time to recurrent VT was 75 days (25th, 75th: 51, 89) in the ablation arm and 57 days (30, 145) in the antiarrhythmic arm. Four patients died, 2 in each arm. Conclusion This clinical trial shows that most patients in clinical practice have already failed antiarrhythmic drug therapy before catheter ablation is considered, and the VT recurrence rates and death in these patients are high. For a large clinical trial to be feasible, factors limiting early consideration of catheter ablation need to be identified and addressed.